MIGRATION PROCESSES AND NATIONAL ELITES - Parkhomenko, Natalia (Київський національний університет імені Тараса Шевченка, 2018)
In the conditions of globalization, the intensification of relations between different States is taking place; the formation of a common market of capital, technologies and goods is formed. In this merged market there is a segment of the labor market, in which intellectual migration plays an extremely important role. At the present phase, migration processes attract more and more attention of scientists in all leading countries of the world. A special place takes intellectual migration. Human bieng, the human factor, especially their intellect, the educational potential has become a real capital. And migration itself forms the bulk of this capital. Migration is becoming more and more differentiated in terms of educational, qualification and professional characteristics, constantly involving new categories and groups of people in the staffing exchange. From ancient times, intellectual migration has been characterized by the constant movement of scientific staff between universities, which, obviously, determined the growth of prestige and the scientific, educational level of a university. Even in the history of Ukraine we can mention Yury Drohobych (Kotermak), professor and rector of the University of Bologna, professor of the Jagiellonian University, Mykhailo Drahomanov, professor at the Higher School in Sofia (now - Sofia University), etc. The present dictates similar needs in intelligence, which is addressed by promising scientists in the search for self-realization. Disproportionately smaller is the "flow" of scientific personnel to Ukraine. But such examples also take place. James Mace, a well-known historian, political scientist, researcher of the Holodomor, moved to Ukraine for scientific research and linked his scientific and livelihood with our country. In Ukraine, such migration processes are characterized by dynamism, diversity and a set of causes, not only of internal scientific, but also socio-economic nature. Over the past decades, part of the scientists who were unable to adapt to the new socio-economic conditions of post-Soviet Ukraine and could not "stay in science" by migrating to other areas of human activity, for example, in business or migrating to other countries. This, in turn, led to an imbalance in the scientific and educational spheres, and created new challenges and threats to the national educational and scientific sector, which affected the level of technical and technological development of Ukraine. The main goals of this paper is to determine the specifics of migration processes in the intellectual sphere, to identify their causes and social mechanisms, to analyze general and special factors of intellectual migration, to identify trends in intellectual migration and to create the appropriate conditions for the development of intellectual potential of Ukraine. Modern international intellectual migration is made up of two parts: highly qualified specialists who migrate from one developed country to another (mainly within Europe) and from specialists from Asia, Africa, Latin America and Eastern Europe. Developing countries (this group can be safely attributed to Ukraine), as a result of the "outflow of intelligence" are experiencing great complications due to the lack of high-skilled and secondary education. That is why the "outflow of intelligence" is seen as the migration of highly skilled and talented specialists from poor and / or isolated countries to industrial centers. This process is permanent, and is steadily gaining momentum, increasing the flows of highly skilled migrants to the European Union States, and especially the United States of America. Key words: intellectual migration, «brain drain», «pull-push» factors, highly skilled workers.

В умовах глобалізації відбувається інтенсифікація відносин між різними державами, формується спільний ринок капіталів, технологій і товарів. На цьому єдиному ринку існує сегмент ринку праці, в якому надзвичайно важливу роль. відіграє інтелектуальна міграція. На сучасному етапі міграційні процеси привертають все більшу увагу учених у всіх провідних країнах світу. Особливе місце займає інтелектуальна міграція. Людина, людський фактор, особливо її інтелект, навчальний потенціал, став справжнім капіталом. Сама міграція являє собою основну частину цього капіталу. Міграція стає все більш диференційованою з точки зору освітніх, кваліфікаційних та професійних характеристик, постійно залучаючи нові категорії та групи людей до кадрового обміну. З давніх часів інтелектуальна міграція характеризувалася постійним рухом наукових кадрів між університетами, що визначало зростання престижу та науково-освітнього рівня університету. «Відплив інтелекту» розглядається як міграція висококваліфікованих таталановитих фахівців з бідних країн у промислові центри. Цей процес є постійним і неухильно набирає обертів, збільшуючи потоки висококваліфікованих мігрантів до Сполучених Штатів Америки та країн Європейського Союзу. Упродовж останніх десятиліть частина вчених, які не змогли пристосуватися до нових соціально-економічних умов пострадянської України і не могли «залишатися в науці» шляхом міграції в інші сфери людської діяльності, наприклад, у бізнес або переміщення в інші країни. Це, у свою чергу, призвело до дисбалансу в науковій і освітній сферах, а також створило нові виклики та загрози національному освітньому та науковому сектору, що вплинуло на рівень технічного та технологічного розвитку України. Стаття присвячена аналізу особливостей, причин, соціальних механізмів та чинників інтелектуальної міграції як особливого міграційного явища, а також досліджує основні міграційні тенденції в Україні та можливості створення умов для розвитку інтелектуального потенціалу України.  Ключові слова: еліта, міграційні процеси, інтелектуальна міграція, «відплив інтелекту», висококваліфіковані працівники.
МІГРАЦІЙНІ ПРОЦЕСИ ТА НАЦІОНАЛЬНІ ЕЛІТИ